Investigation of β-CdP₂ crystals by laser spectroscopy methods - Patskun, I.I.; Slipukhina, I.A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2004)
β-CdP₂ CdP₂ single crystal of tetragonal modification is investigated by methods of lasermodulated spectroscopy at 293 K. The spectra of coherent two-photon absorption (TPA) have been measured and their theoretical analysis has been carried out. Double resonance of TPA at the total energy of two photons 2.60 eV is observed which occur through impurity level d3 in the gap at energy Ec - 0.86 eV (Ec is the energy of the conduction band edge). The time of transverse relaxation of electrons is found to be equal to 4.3*10⁻¹⁴ s. The dependence is observed of single resonance on mutual orientation of vector of linear polarized light and crystallographic axis enabling us to conclude that the single TPA resonance in CdP₂ occurs between the states Г₇(Г₄) → Г₇(Г₃), Г₇(Г₅) → Г₇(Г₃), Г₆(Г₅) → Г₆(Г₁) in the case of the total energy of two photons is ranged from 2.5 to 3.11 eV. The energies of the states mentioned above are obtained. Remove selected